Estimation of correlations in portfolio credit risk models based on noisy security prices - Boudreault, Mathieu; Gauthier, Geneviève; Thomassin, Tommy (Journal of Economic Dynamics and Control, 2015)

Contagion effect on bond portfolio risk measures in a hybrid credit risk model - Boudreault, Mathieu; Gauthier, Geneviève; Thomassin, Tommy (Finance Research Letters, 2014)

Recovery rate risk and credit spreads in a hybrid credit risk model - Boudreault, Mathieu; Gauthier, Geneviève; Thomassin, Tommy (The Journal of Credit Risk, 2013)

Firm-specific credit risk estimation in the presence of regimes and noisy prices - Bégin, Jean-François; Boudreault, Mathieu; Gauthier, Geneviève (Finance Research Letters, 2017)

Credit and Systemic Risks in the Financial Services Sector: Evidence From the 2008 Global Crisis - Bégin, Jean‐François; Boudreault, Mathieu; Doljanu, Delia Alexandra; Gauthier, Geneviève (Journal of Risk and Insurance, 2019)
Abstract We develop a portfolio credit risk model that includes firm‐specific Markov‐switching regimes as well as individual stochastic and endogenous recovery rates. Using weekly credit default swap premiums for 35 financial firms, we analyze the credit risk of each of these companies and their statistical linkages, putting emphasis on the 2005–2012 period. Moreover, we study the systemic risk affecting both the banking and insurance subsectors.